Topical Use of Gentamicin in Potentially Contaminated Laparoscopic Cholecystectomy After Bile Spillage During Gall Bladder Retrieval - Ali, Afaque; Hussain, Zaki; Jamal, Ayesha; Rahat, Fatima; Shoof, Talha Mak; Islam, Saqib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To observe the effects of topical Gentamycin as a prophylactic measure to control post-operative port site infection after bile spillage during gall bladder retrieval in patients undergoing laparoscopic cholecystectomy.Study Design: Quasi-experimental study.Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi, from Feb to Aug 2019.Methodology: The study population comprised 80 patients (divided into two groups) diagnosed with cholelithiasis and underwent elective laparoscopic cholecystectomy. Seven surgeries were converted into open cholecystectomies, and bile spillage was recorded in 42 patients who underwent uneventful surgery. These patients were then examined for 30 days to evaluate port site infection.Results: It was seen that EPSI was more common in patients in the fourth decade of their life even after Gentamicin prophylaxis 6 (14.29%). A deeper analysis of the study showed that EPSI was more common in patients with Class-I obesity and their fourth decade of life. When compared to the gender, we found that the ratio of EPSI was higher in the female population (1:2) as compared to males (1:4).Conclusion: In our research, topical use of Gentamicin in potentially contaminated laparoscopic cholecystectomy after bile spillage during gall bladder retrieval proved beneficial.